Analysis of Interest of UIN Fatmawati Sukarno Bengkulu Students in Investing in Sharia Capital Market - Deni Elva Riani; Inna Rampasi; Teuku Muhammad Faridz R.; Madhav Karki (Yayasan Darussalam Bengkulu, 2024)
The emergence of Islamic capital markets is key to reducing the risk of uncertainty in conventional capital markets and also reducing financial scandals in international capital markets. The following is the cause of students' reluctance to invest in the capital market as from the results of the minimal capital research does not have a negative and insignificant effect on student interest. In this study using a qualitative approach with the type of obeservation research. The population of this study were students of UIN Fatmawati Sukarno Bengkulu with a sample of 10 students. The results of this study indicate that UINFAS students' interest in investing in the Islamic capital market is influenced by several factors, namely knowledge, income level, motivation and risk. This study is limited to the use of decision-making variables that influence interest in investing in the capital market.